Thyroid Hemiagenesis with Ipsilateral Parathyroid Adenoma; Case report with Review of the Literature - Alnaser, Mumtaz K (AL-Kindy College Medical Journal, 2020)
Thyroid hemiagenesis (THA) is a rare congenital anomaly in which one lobe of thyroid gland fails to develop during embryological stage. Agenesis may be unilateral, total or isthmic. Left thyroid lobe is more commonly involved than right lobe in hemiagenesis. Agenesis of the isthmus was seen in 50% of cases. Left sided hemiagenesis is more common than right sided hemiagenesis with a Left to right ratio of 4:1. Clinically patients can be euthyroid, hypothyroid or hyperthyroid. Often it is diagnosed as an incidental finding during ultrasonography (USG) study of neck, which can easily diagnose this condition.Actual incidence of THA is unknown; most cases are diagnosed in patients admitted for thyroid scan or thyroid surgery because of suspicion of other thyroid abnormalities. This explains high frequency of association of hemiagenesis with other thyroid abnormalities such as multinodular goiter, adenoma, hyperthyroidism, hypothyroidism, chronic thyroiditis, and carcinoma.Khaladkar, et al. emphasized that surgeon when planning a thyroidectomy must be aware of rare anatomical variations because such anomalies are not noticed in the differential diagnosis, investigations and treatment.We report a rare case of 46 years old female patient who presented with nontoxic nodular goiter and intraoperatively we found a right sided multinodular goiter including the isthmus with complete absence of the left thyroid lobe with ipsilateral inferior parathyroid adenoma which is according to the available studies is the sixth case recorded worldwide till now.